Young Age Is a Positive Prognostic Factor for Residual Hearing Preservation in Conventional Cochlear Implantation. Issue 1 (January 2015) - Anagiotos, Andreas; Hamdan, Nadin; Lang-Roth, Ruth; Gostian, Antoniu-Oreste; Lüers, Jan-Christoffer; Hüttenbrink, Karl-Bernd; Beutner, Dirk
<x xml:space="preserve">Abstract</x> Objective To investigate the prognostic significance of various factors in hearing preservation after traditional cochlear implantation (CI). Study design Retrospective case review. Setting Academic tertiary referral center. Patients A total of 153 implantations with mean patient age at implantation of 36 years (from 10 mo to 83 yr) and residual hearing at the frequencies 250, 500, and 1, 000 Hz on the unaided preoperative pure-tone audiometry were included. Intervention(s) CI with a conventional full-length electrode. Main outcome measure(s) The changes on the residual hearing 3 months after implantation were analyzed regarding patients' demographic factors, shape of the preoperative threshold curve, type of the electrode carrier, and approach of electrode insertion in the cochlea. Preservation of residual hearing was defined as measurable postoperative threshold at the frequencies 250, 500, and 1, 000 Hz. Results Preservation of residual hearing was observed in almost half of the cases (47%). In more than half of these patients (54%), a maximal to complete hearing preservation (0–10 dB loss) was achieved. About one-third of these implantations (29%) showed a moderate preservation of residual hearing (11–20 dB loss). In the remaining 17%, the preservation of hearing was marginal (>21 dB loss). Hearing preservation and its extent were significantly better in children and adolescents compared with those in adults. Conclusion The preservation of residual hearing after conventional CI is possible. Young age seems to have a positive impact on hearing preservation.